Evaluation of a Tai Chi Intervention to Promote Well-Being in Healthcare Staff: A Pilot Study - Marshall, David (Religions, 2018)
Whilst healthcare professions are already considered one of the most stressful occupations, workplaces are becoming busier, and the potential for workplace absenteeism and burnout has intensified. There is growing evidence that the mind-body practice of Tai Chi, which originated in China as a martial art, has value in treating or preventing many health-related problems, such as stress and anxiety, and that regular practice helps to significantly improve wellbeing, attention, focus, and resilience. This intervention provided 12 sessions of Tai Chi for a group of 12 multidisciplinary healthcare workers and was general wellbeing was measured pre- and post-intervention. Using a mixed methods research design, it was discovered that there were statistically significant gains in well-being during this timeframe with results indicating a strong case for further roll out of the program to a larger pool and more extensive study.